WSES Guidelines for the management of acute left sided colonic diverticulitis in the emergency setting - Sartelli, Massimo; Catena, Fausto; Ansaloni, Luca; Coccolini, Federico; Griffiths, Ewen A; Abu-Zidan, Fikri M; Di Saverio, Salomone; Ulrych, Jan; Kluger, Yoram; Ben-Ishay, Ofir; Moore, Frederick A; Ivatury, Rao R; et al. (World journal of emergency surgery, 2016)
Acute left sided colonic diverticulitis is one of the most common clinical conditions encountered by surgeons in acute setting. A World Society of Emergency Surgery (WSES) Consensus Conference on acute diverticulitis was held during the 3rd World Congress of the WSES in Jerusalem, Israel, on July 7th, 2015. During this consensus conference the guidelines for the management of acute left sided colonic diverticulitis in the emergency setting were presented and discussed. This document represents the executive summary of the final guidelines approved by the consensus conference.